Strategi Peningkatan Aksen Visual melalui Pengendalian Kontras Luminansi pada Galeri Semi-Outdoor - Vidiyanti, Christy; Ghassani, Dea Putri (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2025)
Strategies for Enhancing Visual Accents through Luminance Contrast Control in Semi-Outdoor Galleries Lighting is a key element in shaping the visual perception of a gallery. In the semi-outdoor gallery of Kampung Susun Kunir, daylight dominates during the daytime, while artificial lighting is not yet optimal and fails to create visual accents due to limitations in luminaire positioning on the exposed ceiling. This study aims to formulate strategies for enhancing visual accents through luminance contrast control. Simulations using DIALux were conducted to analyze luminance values and ratios, both in surrounding walls (immediate) and vertical surfaces (ambience). The results show that artificial lighting is ineffective during the day; however, interventions in the form of additional spotlights and linear spotlights at night successfully increased visual contrast across display surfaces. These findings underscore the importance of adjusting lighting to spatial conditions and serve as a foundation for developing efficient and adaptive lighting guidelines for community exhibition spaces to support artwork legibility and improve visitors’ visual experience.